The symbolic representation of gender a discursive approach - Lombardo, Emanuela; Meier, Petra (Ashgate Pub., 2014)
Emanuela Lombardo and Petra Meier draw on theories of symbolic representation and gender, as well as rich primary material about political debates on labour and care issues, partnership and reproductive rights, gender violence, and quotas. This important exploration raises relevant new questions regarding the representation of gender that form valuable contributions to the fields of political science, political theory, sociology, and gender studies.